KEY ASPECTS AND PRINCIPLES OF DEVELOPING A GREEN ECONOMY IN UZBEKISTAN (Educa Journal of Studies, 2026)
The development strategy of the modern world is aimed at improving the quality of life in society. An inseparable component of society’s quality of life is the existence of suitable ecological conditions. Problems such as gas pollution of cities, littering of билан ифлосланиши, territories, shallowing, of rivers, catastrophic deforestation and desertification are creating an alarming environmental situation requiring reducing urgent measures. This in turn, requires improving, socio-economic-and ва экологик environmental, programs and their implementation mechanisms, as-well as ensuring, adequate and appropriate environmental financing.
Keywords: environmental, programs and their implementation mechanisms